Pocket world in figures : The economist pocket world in figures 2016 (London, England Profile Books Ltd, 2015)
The 25th annual edition of this perennial favourite has been completely updated, revised and expanded with many new features, including a section exploring the huge global changes since its inception in 1991. Full of facts and figures about the world today - on subjects as diverse as geography, population and demographics, business, finance and the economy, transport, tourism and the environment, society, culture and crime - it is a mine of fascinating data that will both inform and entertain. Where else would you discover in a single volume that: *A Big Mac in Israel will cost you twice as much as one in South Africa. *Qatar has the most obese adult population in the world. *Rwanda, Bolivia and Cuba have the highest proportions of women in parliament. *The world's tallest building, the Burj Khalifa in Dubai, is more than twice the height of the Empire State Building in New York. *The US space budget is more than six times that of its nearest rival, China. With rankings on more than 200 topics, data on more than 190 countries, detailed profiles of more than sixty-five of the world's major economies and special profiles on the Eurozone and the world, Pocket World in Figures is always eagerly awaited by its many thousands of fans. No-one who wants to be well-informed can afford to be without this new edition.
Keywords: Statistics; Economic history $1 (B21st centurys -- Statistics; Economic indicators; Social indicators; Social research & statistics ; Economic statistics ; Yearbooks, annuals, almanacs; REFERENCE / Yearbooks & Annuals; REFERENCE / Almanacs; SOCIAL SCIENCE / Research; SOCIAL SCIENCE / Statistics; BUSINESS & ECONOMICS / Statistics